A strategic integrated healthcare facility management model - Lavy, Sarel; Shohet, Igal M. (International Journal of Strategic Property Management, 2010)
The requirement to reduce expenditure on “non‐core” activities, along with building’s owners’ expectations for improved performance, are the main dilemmas with which a facility manager deals on a regular basis. The primary objective of this research was to identify the effect of defined parameters, such as the actual age of a building and its level of occupancy, on the performance of facilities and their systems. This study contributed to the development of a model capable of integrating these parameters into a Facility Management (FM) tactical and strategic decision‐making process, referred to as the Integrated Healthcare Facility Management Model (IHFMM). The model’s guidelines may be outlined for the methodological design and operation of facilities from a life cycle perspective. The paper presents the architecture of the developed model, and four of the 15 procedures that comprise the heart of this model. First published online: 18 Oct 2010